PECULIARIDADES CRONOLÓGICAS EN LA MONEDA EUROPEA DE LA EDAD MODERNA Y CONTEMPORÁNEA - Francisco Olmos, José María de (Documenta & Instrumenta - Documenta et Instrumenta, 2008)
In this article we will observe how in a number of historical moments of the history of Europe, the dates offered in the coins present certain peculiarities that must be taken into account for a correct interpretation. To be precise we deal with the pieces coined by James II in England and Ireland during his confrontation with William of Orange (1689-1690), called 'gunmoneys', and the ones related to the diffusion of the ideas or the French Revolution, in France as well as in the Italian peninsula, one century later.
Keywords: Historical chronology; James II; William III of Orange; Ireland; Gunmoneys; Boyne´s Battle; French Revolution; Italian Republics; Coins